2016
DOI: 10.1002/anie.201607742
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Pyrroles by Dehydrogenative Coupling of Diols and Amines Catalyzed by Cobalt Pincer Complexes

Abstract: Herein, the first example of base-metal-catalyzed dehydrogenative coupling of diols and amines to selectively form functionalized 1,2,5-substituted pyrroles liberating water and hydrogen gas as the sole by-products is presented. The reaction is catalyzed by pincer complexes of earth-abundant cobalt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
80
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(81 citation statements)
references
References 75 publications
0
80
0
1
Order By: Relevance
“…[1] Alcohols can be obtained from indigestible and abundantly available lignocellulose biomass, [2,3] and thus the development of alcohol re-functionalization reactions can contribute to the conservation of our fossil carbon resources and the reduction of CO 2 emissions.A variety of reactions have been developed recently to catalytically synthesize aromatic N-heterocyclic compounds,s uch as pyrroles, [4,5] pyridines, [6] pyrimidines, [7] and others, [8] from alcohols. Amore sustainable approach would be the use of catalysts based on abundantly available 3d metals,s uch as Co,F e, and Mn (nonprecious or base metals), to additionally conserve our rare noble metal resources.M ilstein and co-workers recently introduced ac obalt-catalyzed synthesis of pyrroles from diols and amines [10] (Scheme 1, top). Amore sustainable approach would be the use of catalysts based on abundantly available 3d metals,s uch as Co,F e, and Mn (nonprecious or base metals), to additionally conserve our rare noble metal resources.M ilstein and co-workers recently introduced ac obalt-catalyzed synthesis of pyrroles from diols and amines [10] (Scheme 1, top).…”
mentioning
confidence: 99%
“…[1] Alcohols can be obtained from indigestible and abundantly available lignocellulose biomass, [2,3] and thus the development of alcohol re-functionalization reactions can contribute to the conservation of our fossil carbon resources and the reduction of CO 2 emissions.A variety of reactions have been developed recently to catalytically synthesize aromatic N-heterocyclic compounds,s uch as pyrroles, [4,5] pyridines, [6] pyrimidines, [7] and others, [8] from alcohols. Amore sustainable approach would be the use of catalysts based on abundantly available 3d metals,s uch as Co,F e, and Mn (nonprecious or base metals), to additionally conserve our rare noble metal resources.M ilstein and co-workers recently introduced ac obalt-catalyzed synthesis of pyrroles from diols and amines [10] (Scheme 1, top). Amore sustainable approach would be the use of catalysts based on abundantly available 3d metals,s uch as Co,F e, and Mn (nonprecious or base metals), to additionally conserve our rare noble metal resources.M ilstein and co-workers recently introduced ac obalt-catalyzed synthesis of pyrroles from diols and amines [10] (Scheme 1, top).…”
mentioning
confidence: 99%
“…Based on these initial findings,avariety of noble-metalcatalyzed reactions for the conversion of alcohols into N-heterocycles have been developed. Milstein and co-workers showed very recently that aC o complex efficiently catalyzes the synthesis of pyrroles from diols and amines, [11] ar eaction originally introduced by the Crabtree group with aR uc atalyst (Scheme 1, top). It would be highly desirable to combine both sustainability concepts and develop catalysts based on abundantly available transition metals,s uch as Mn, Fe,a nd Co (base or nonprecious metals), for the conversion of alcohols into N-heterocycles.…”
mentioning
confidence: 99%
“…The addition of 18‐crown‐6 into the reaction of 4 a with 2 a remarkably suppressed the formation of amine 3 a (Equation 5). These results indicated that K + ion was engaged in the transfer hydrogenation reaction of imine to secondary amine, due to its ionic radius being larger than that of Na + and their different coordination effects ,. The interaction of K + with imine might lengthen C=N bond, which could be readily hydrogenated by Ru catalyst.…”
Section: Resultsmentioning
confidence: 94%